Positive electrode material for lithium secondary battery, preparation method of positive electrode material, positive electrode plate, secondary battery, use method of secondary battery and electric device

By using a modified body or a cladding layer containing lithium supplement agent in the positive electrode material of lithium secondary battery, the problems of poor conductivity and serious polarization of the positive electrode material in the prior art are solved, and a higher energy density and cycle life are achieved.

CN119852331APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311335261.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The positive electrode materials of existing lithium secondary batteries have poor conductivity and are prone to polarization, resulting in low energy density of the battery cell and poor circulation performance.

Method used

The modified body or coating layer containing the lithium supplement agent LiyMOd is used to modify or coat the matrix containing the positive electrode active material LixAsMn1-sP1-zEzO4 to improve the distribution uniformity of the lithium supplement agent and the contact area with the electrolyte.

Benefits of technology

The conductivity of the positive electrode material is improved, the degree of polarization is reduced, the amount of deliquency is increased, and the energy density and cycle life of the secondary battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852331A_ABST
    Figure CN119852331A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material for a lithium secondary battery, a preparation method of the positive electrode material, a positive electrode plate, a secondary battery, a use method of the secondary battery and an electric device. The positive electrode material for the lithium secondary battery comprises a substrate and a modification body arranged on the surface of the substrate, the matrix comprises Li < x > As < Mn < 1-s > P < 1-z > C < z > O < 4 >, x is smaller than or equal to 1.1, 0lt; x is greater than or equal to 1 and less than or equal to 1, s is greater than or equal to 0 and less than or equal to 0.1, z is greater than or equal to 0 and less than or equal to 0.1, A comprises one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and C comprises one or more elements selected from B (boron), S, Si and N; the modification body comprises LiyMOd, and wherein 1lt; y < = 61lt; d is smaller than or equal to 4, and M comprises one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb and Cr.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular, to a cathode material for a lithium secondary battery, a preparation method of the cathode material for a lithium secondary battery, a cathode electrode sheet, a secondary battery and its usage method, and an electrical device. Background Art

[0002] In recent years, with the increasingly wide application range of secondary batteries, secondary batteries are widely used in energy storage power systems such as hydraulic, thermal, wind, and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. Due to the great development of secondary batteries, higher requirements are also put forward for their energy density, cycle performance, etc. Summary of the Invention

[0003] The present application is made in view of the above problems, and its purpose is to provide a cathode material for a lithium secondary battery, a preparation method of the cathode material, a cathode electrode sheet, a secondary battery, a usage method of the secondary battery, and an electrical device. The cathode material of the present application has high conductivity, reduces the polarization degree of the secondary battery, increases the lithium deintercalation amount of the cathode material, and improves the energy density of the secondary battery.

[0004] To achieve the above object, in the first aspect of the present application, a cathode material for a lithium secondary battery is provided, including a matrix and a modifier disposed on the surface of the matrix; the matrix includes Li x A s Mn 1-s P 1-z E z O4, where 0 < x ≤ 1.1, 0 < s ≤ 1, 0 ≤ z ≤ 0.1, the A includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge; the E includes one or more elements selected from B (boron), S, Si, N; the modifier includes Li y MO d , where 1 < y ≤ 6, 1 < d ≤ 4, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, Cr, and the valence state of at least one metal element in the M is lower than its own highest oxidation state.

[0005] Thus, by using a modifier containing a lithium supplement agent Li y MO d disposed on a cathode active material containing Li x A s Mn 1- s P 1-z Ez On the matrix surface of O4, the uniformity of the lithium supplement agent distribution in the cathode material is improved, the contact area between the lithium supplement agent and the electrolyte is increased, the electrical conductivity of the cathode material is enhanced, the polarization degree of the secondary battery is reduced, the lithium deintercalation amount of the cathode material is increased, and the energy density of the secondary battery is improved.

[0006] In any embodiment, the cathode material for a lithium secondary battery includes a core and a coating layer that coats the core; the core includes Li x A s Mn 1-s P 1-z E z O4, where 0 < x ≤ 1.1, 0 < s ≤ 1, 0 ≤ z ≤ 0.1, the A includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge, and the E includes one or more elements selected from B (boron), S, Si, N; the coating layer includes Li y MO d , where 1 < y ≤ 6, 1 < d ≤ 4, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, Cr, and the valence state of at least one metal element in the M is lower than its own highest oxidation valence state.

[0007] Thus, in this application, by using a coating layer containing the lithium supplement agent Li y MO d to coat the core containing the cathode active material Li x A s Mn 1- s P 1-z E z O4, the uniformity of the lithium supplement agent distribution in the cathode material is improved, the contact area between the lithium supplement agent and the electrolyte is increased, the electrical conductivity of the cathode material is enhanced, the polarization degree of the secondary battery is reduced, the lithium deintercalation amount of the cathode material is increased, and the energy density of the secondary battery is improved.

[0008] In any embodiment, the modifier or the coating layer includes Li y MnO2, Li y NbO4, Li y FeO4, Li y CoO4, Li y NiO2, Li y CuO2, Li y Cu x1 Ni 1-x1-y1 M’ y1One or more of O2, wherein each y is independently greater than 1 and less than or equal to 6, 0 < x1 < 1, 0 ≤ y1 < 0.1, and the M' includes one or more elements of Zn, Sn, Mg, Fe, and Mn; optionally, the modifier or the coating layer includes Li 1.8 MnO2, Li6CoO4, Li y NiO2, Li2Cu 0.6 Ni 0.4 One or two of O2.

[0009] In any embodiment, the matrix or the core includes Li x D s1 Fe s2 Mn 1-s1-s2 PO4, wherein 0 < x ≤ 1, s1 ≥ 0, s2 > 0, 0 < s1 + s2 ≤ 1; the D includes one or more elements of Ti, V, Zr, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge, and is optionally one or two elements of Ti and V; the modifier or the coating layer includes Li y NiO2, wherein 1 < y < 2.

[0010] Thereby, the conductivity of the positive electrode material is improved, the polarization degree is reduced, the lithium deintercalation amount of the positive electrode material is increased, and the energy density and cycle life of the secondary battery are improved.

[0011] In any embodiment, the average diameter of the matrix or the core is 0.7 - 12 μm, and is optionally 1 - 10 μm; and / or,

[0012] The average thickness of the modifier or the coating layer is 10 - 30 nm, and is optionally 10 - 15 nm.

[0013] Thereby, through the above size design, the positive electrode material has high conductivity on the one hand, increases the lithium deintercalation amount of the positive electrode material, thereby improving the energy density and the first Coulomb efficiency of the battery cell, and on the other hand, part of the active lithium ions are retained in the lithium supplement agent and are gradually released and deintercalated during the subsequent charge and discharge processes to realize lithium supplementation of the positive electrode sheet, thereby prolonging the cycle life of the battery.

[0014] In any embodiment, the mass ratio of the Li y MO d to the Li x A s Mn 1-s P 1-z E z O4 is 0.5% - 8%, and is optionally 1% - 5%.

[0015] As a result, the energy density of the battery cell is increased while the cycle life of the battery is extended.

[0016] The BET specific surface area of ​​the positive electrode material is 0.9-11.1 m 2 / g, optional 7-10.7m 2 / g.

[0017] In this way, the balance between the initial lithium desorption and the subsequent lithium release is maintained, thus extending the cycle life of the battery.

[0018] In any embodiment, the modified body or the coating layer further comprises a carbonaceous material, wherein the carbonaceous material is coated on the Li y MO d surface; and / or,

[0019] The matrix or the core also includes a carbonaceous material, and the carbonaceous material is coated on the Li x A s Mn 1-s P 1- z C z O4 surface; and / or, the carbonaceous material includes one or more of conductive carbon, graphene, and carbon nanotubes.

[0020] It is beneficial to improve the conductivity of the positive electrode material.

[0021] The second aspect of the present application also provides a method for preparing a positive electrode material for a lithium secondary battery, which is method one or method two;

[0022] The method 1 comprises:

[0023] Li x A s Mn 1-s P 1-z E z O4 and Li y MO d Mixing and calcining to obtain a positive electrode material for a lithium secondary battery;

[0024] The second method comprises:

[0025] Li x A s Mn 1-s P 1-z E z O4 is mixed with any one selected from a lithium source and a source of an M element, and roasted to obtain an intermediate product;

[0026] The intermediate product is mixed with another source selected from a lithium source and a source of an M element, and calcined to obtain a positive electrode material for a lithium secondary battery;

[0027] Among them, the positive electrode material for the lithium secondary battery includes a core and a coating layer that coats the core; the core includes Li x A s Mn 1-s P 1-z E z O4, where 0 < x ≤ 1.1, 0 < s ≤ 1, 0 ≤ z ≤ 0.1, the A includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge, and the E includes one or more elements selected from B (boron), S, Si, N; the coating layer includes Li y MO d , where 1 < y ≤ 6, 1 < d ≤ 4, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, Cr, and the valence state of at least one metal element in the M is lower than its own highest oxidation state.

[0028] Thus, in this application, by coating the core containing the positive electrode active material Li y MO d with a coating layer containing the lithium supplement agent Li x A s Mn 1-s P 1- z E z O4, the uniformity of the distribution of the lithium supplement agent in the positive electrode material is improved, the contact area between the lithium supplement agent and the electrolyte is increased, the conductivity of the positive electrode material is improved, the polarization degree is reduced, the lithium deintercalation amount of the positive electrode material is increased, and the energy density of the battery cell is increased.

[0029] In any implementation manner, in the method one,

[0030] the Dv50 particle size of the Li y MO d is 8 - 25 nm, and can be optionally 8 - 10 nm; and / or,

[0031] the Dv50 particle size of the Li x A s Mn 1-s P 1-z E z O4 is 0.1 - 10 μm, and can be optionally 0.5 - 5 μm; and / or,

[0032] the Li y MO d and the Li x A s Mn 1-s P 1-z Ez The mass proportion of O4 is 0.5%-8%, optionally 1%-5%; and / or,

[0033] The calcination temperature is 400°C-1200°C, and can be 600°C-1200°C; and / or,

[0034] The calcination time is 30-65 hours; and / or,

[0035] Mixing is performed by a coating machine at a speed of 50-400 rpm; and / or,

[0036] The mixing time is 3-10 hours; and / or,

[0037] The method 1 further comprises: before mixing, coating the Li y MO d and / or Li x A s Mn 1-s P 1- z E z O4; and / or,

[0038] The carbonaceous material includes one or more of conductive carbon, graphene, and carbon nanotubes.

[0039] By Li y MO d and Li x A s Mn 1-s P 1-z E z O4 is formulated with the above-mentioned particle size ratio. On the one hand, it can regulate the rate performance of the material, and on the other hand, it can maintain a balance between the initial lithium removal amount and the subsequent lithium release amount, and avoid the introduction of residual alkali, thereby improving the energy density of the battery cell and extending the cycle life of the battery.

[0040] In any embodiment, in the method 2,

[0041] The lithium source includes one or more of lithium hydroxide, lithium oxide, and lithium carbonate; and / or,

[0042] The source of the M element includes one or more of the hydroxide, sulfate, nitrate, chloride, and oxide of the M element; and / or,

[0043] The calcination temperature is independently 400°C-800°C; and / or,

[0044] The calcination time is independently 30-65 hours; and / or,

[0045] Mixing is performed by a coating machine, and the speed of mixing is independently 300-400 rpm; and / or,

[0046] The mixing time was independently 4-6 hours.

[0047] A third aspect of the present application provides a positive electrode plate, comprising the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the method of the second aspect of the present application.

[0048] The fourth aspect of the present application provides a secondary battery, comprising the positive electrode sheet of the third aspect of the present application.

[0049] In any embodiment, the upper limit voltage of the secondary battery for charging is 3.65-3.85 V; optionally, the lower limit voltage of the secondary battery for discharging is 2.0-2.5 V. Thus, the oxidative decomposition of the electrolyte can be reduced, and some active lithium ions in the lithium supplement agent are gradually released in subsequent cycles, thereby extending the cycle life of the battery.

[0050] A fifth aspect of the present application provides an electrical device, comprising the secondary battery of the fourth aspect of the present application.

[0051] A sixth aspect of the present application provides a method for using a secondary battery, which is charged with an upper limit voltage in the range of 3.65-3.85V and optionally discharged with a lower limit voltage in the range of 2.0-2.5V; wherein the secondary battery includes the positive electrode sheet of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0053] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0054] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0055] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0056] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0057] Figure 6 It is a schematic diagram of an electrical device using a battery cell according to an embodiment of the present application as a power source.

[0058] Description of reference numerals:

[0059] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0060] Hereinafter, the embodiments of the positive electrode material and preparation method thereof, positive electrode sheet, battery, method of using the battery, battery module, battery pack and electrical device of the present application will be specifically disclosed with appropriate reference to the drawings. However, there will be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0061] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0062] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0063] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0064] Unless otherwise specified, all steps of this application can be carried out sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), indicating that the method may include steps (a) and (b) carried out sequentially, or may also include steps (b) and (a) carried out sequentially. For example, it is mentioned that the method may further include step (c), indicating that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or may also include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.

[0065] [Battery cell]

[0066] A battery cell, also known as a rechargeable battery or a storage battery, refers to a battery that can activate the active material through charging after discharging and can be used continuously.

[0067] Generally, a battery cell includes a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. During the charge and discharge process of the battery, active ions (such as lithium ions) are embedded and extracted back and forth between the positive electrode plate and the negative electrode plate. The separator is disposed between the positive electrode plate and the negative electrode plate, mainly playing a role in preventing short circuit between the positive and negative electrodes, and at the same time allowing active ions to pass through. The electrolyte is between the positive electrode plate and the negative electrode plate, mainly playing a role in conducting active ions.

[0068] [Positive electrode material]

[0069] An embodiment of the present application provides a positive electrode material for a lithium secondary battery, including a matrix and a modifier disposed on the surface of the matrix; the matrix includes Li x A s Mn 1-s P 1-z E z O4, where 0 < x ≤ 1.1, 0 < s ≤ 1, 0 ≤ z ≤ 0.1, the A includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge; the E includes one or more elements selected from B (boron), S, Si, N; the modifier includes Li y MO d , where 1 < y ≤ 6, 1 < d ≤ 4, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, Cr, and the valence state of at least one metal element in the M is lower than its own highest oxidation state.

[0070] In the prior art, a lithium supplement agent is usually mixed with a positive electrode active material to prepare a positive electrode material. However, the prepared positive electrode material has disadvantages such as poor conductivity, easy polarization during charge and discharge, and low energy density of the battery cell.

[0071] Although the mechanism is not yet clear, the applicant unexpectedly found that: in this application, by using a modifier containing a lithium supplement agent Li y MO d and disposing it on the surface of the matrix containing the cathode active material Li x A s Mn 1-s P 1-z E z O4, the uniformity of the distribution of the lithium supplement agent in the cathode material is improved, the contact area between the lithium supplement agent and the electrolyte is increased, the conductivity of the cathode material is increased, the polarization degree of the secondary battery is reduced, the lithium extraction amount of the cathode material is increased, and the energy density of the secondary battery is increased.

[0072] In any embodiment, the cathode material for a lithium secondary battery includes a core and a coating layer that coats the core; the core includes Li x A s Mn 1-s P 1-z E z O4, where 0 < x ≤ 1.1, for example, x is 0.1, 0.2, 0.4, 0.5, 0.7, 0.8, 0.9, 1, 1.1 or a range composed of any of the above values, 0 < s ≤ 1, for example, s is 0.1, 0.2, 0.4, 0.5, 0.7, 0.8, 0.9, 1 or a range composed of any of the above values, 0 ≤ z ≤ 0.1, for example, z is 0, 0.01, 0.03, 0.05, 0.07, 0.08, 0.09, 0.1 or a range composed of any of the above values, A includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge, and E includes one or more elements selected from B (boron), S, Si, N; the coating layer includes Li y MO d , where 1 < y ≤ 6, y is for example 1.1, 1.2, 1.5, 1.8, 2, 3, 4, 5, 6 or a range composed of any of the above values, 1 < d ≤ 4, for example, d is 1.1, 1.3, 1.5, 1.7, 2, 3, 4 or a range composed of any of the above values, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, Cr, and the valence state of at least one metal element in M is lower than its own highest oxidation state.

[0073] Although the mechanism is not yet clear, the applicant unexpectedly found that: in this application, by using a coating layer containing a lithium supplement agent Li y MO d to coat the cathode active material Li x A sMn 1-s P 1-z E z The core of O4 improves the uniformity of the distribution of the lithium supplement in the cathode material, increases the contact area between the lithium supplement and the electrolyte, enhances the electrical conductivity of the cathode material, reduces the polarization degree of the secondary battery, increases the lithium deintercalation amount of the cathode material, and improves the energy density of the secondary battery.

[0074] In some embodiments, the modifier or the coating layer comprises Li y MnO2, Li y NbO4, Li y FeO4, Li y CoO4, Li y NiO2, Li y CuO2, Li y Cu x1 Ni 1-x1-y1 M’ y1 One or more of O2, wherein each of the y is independently greater than 1 and less than or equal to 6, 0 < x1 < 1, 0 ≤ y1 < 0.1, and the M’ comprises one or more elements of Zn, Sn, Mg, Fe, Mn; optionally, the modifier or the coating layer comprises Li 1.8 MnO2, Li6CoO4, Li y NiO2, Li2Cu 0.6 Ni 0.4 One or two of O2.

[0075] In some embodiments, the matrix or the core comprises Li x D s1 Fe s2 Mn 1-s1-s2 PO4, wherein 0 < x ≤ 1, for example, x is 0.1, 0.2, 0.4, 0.5, 0.7, 0.8, 0.9, 1 or a range composed of any of the above values; s1 ≥ 0, s2 > 0, 0 < s1 + s2 ≤ 1, and s1 + s2 is, for example, 0.1, 0.2, 0.4, 0.5, 0.7, 0.8, 0.9, 1 or a range composed of any of the above values; the D comprises one or more elements of Ti, V, Zr, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge, and may be optionally one or two elements of Ti, V; the modifier or the coating layer contains Li y NiO2, wherein 1 < y < 2, and y is, for example, 1.1, 1.2, 1.5, 1.8 or a range composed of any of the above values.

[0076] As a result, the uniformity of the distribution of the lithium supplement in the positive electrode material is improved, the contact area between the lithium supplement and the electrolyte is increased, the conductivity of the positive electrode material is improved, the polarization degree is reduced, the lithium removal amount of the positive electrode material is increased, and the energy density of the battery cell is improved.

[0077] In some embodiments, the average diameter of the matrix or core is 0.7-12 μm, optionally 1-10 μm, for example 0.7 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or a range consisting of any of the above values; and / or, the average thickness of the modified body or coating is 10-30 nm, optionally 10-15 nm, for example 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm or a range consisting of any of the above values.

[0078] Therefore, through the above-mentioned size design, on the one hand, the positive electrode material has high conductivity, which increases the lithium removal amount of the positive electrode material, thereby improving the energy density of the battery cell and the first coulomb efficiency of the battery. On the other hand, some active lithium ions are retained in the lithium replenisher, which are gradually released during the subsequent charging and discharging process, thereby replenishing the lithium of the positive electrode plate, thereby extending the cycle life of the battery.

[0079] In the present invention, the average diameter of the kernel and the average thickness of the coating layer are tested by conventional methods in the art. For example, TEM is used to test the positive electrode material. Since the kernel and the coating layer of a single material particle present different lattices under TEM, the interface between the kernel and the coating layer can be observed, and then the kernel diameter and the coating layer thickness of a single material particle are measured in combination with mapping (TEM's own software), and a total of multiple (e.g., 50-60) material particles are measured, and the average kernel diameter and the average coating layer thickness of all material particles are calculated to obtain the average kernel diameter and the average coating layer thickness.

[0080] In the present invention, "coating" can be partial coating or full coating; wherein, "partial coating" means that the coating layer covers part of the surface of the core; and "full coating" means that the coating layer covers the entire surface of the core.

[0081] In some embodiments, the Li y MO d (For example, Li y NiO2) and the Li x A s Mn 1-s P 1-z E z O4 (such as Li xThe mass proportion of FePO4 is 0.5%-8%, and can be optionally 1%-5%, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or a range consisting of any of the above values.

[0082] As a result, the energy density of the battery cell is increased while the cycle life of the battery is extended.

[0083] In some embodiments, the BET specific surface area of ​​the positive electrode material is 0.9-11.1 m 2 / g, optional 7-10.7m 2 / g, for example 0.9m 2 / g, 1.0m 2 / g, 2.0m 2 / g, 3.0m 2 / g, 4.0m 2 / g, 5.0m 2 / g, 6.0m 2 / g, 7.0m 2 / g, 8.0m 2 / g, 9.0m 2 / g, 10.0m 2 / g, 11.0m 2 / g or any range consisting of the above values.

[0084] In this way, the balance between the initial lithium desorption and the subsequent lithium release is maintained, extending the cycle life of the battery.

[0085] In the present application, the BET specific surface area of ​​the positive electrode material is tested by conventional methods in the field. For example, the test is carried out with reference to the standard GB / T19587-2004 "Determination of the specific surface area of ​​solid substances by gas adsorption BET method". Specifically, take the sample to be tested and put it into the sample tube, and record the initial mass of the sample to be tested. Load the sample to be tested into the specific surface area analyzer, start degassing, and heat the sample to be tested to 200°C for 2h, and then record the mass of the sample to be tested after degassing. Then reload the degassed sample to be tested into the equipment, pour in liquid nitrogen for BET testing. Set the nitrogen pressure to 0.08MPa-0.12MPa. After the test, calculate the BET specific surface area from the test results.

[0086] In some embodiments of the present application, Li x A s Mn 1-s P 1-z C z O4、Li y MO d The surface of the nanostructured carbon fiber may be independently coated with other materials such as carbonaceous materials.

[0087] In some embodiments, the modified body or the coating layer further comprises a carbonaceous material, wherein the carbonaceous material is coated on the Li y MO d surface; and / or,

[0088] The matrix or the core also includes a carbonaceous material, and the carbonaceous material is coated on the Li x A s Mn 1-s P 1- z C z O4 surface; and / or, the carbonaceous material includes one or more of conductive carbon, graphene, and carbon nanotubes.

[0089] It is beneficial to improve the conductivity of the positive electrode material.

[0090] [Method for preparing positive electrode material]

[0091] One embodiment of the present application provides a method for preparing a positive electrode material for a lithium secondary battery, which is method one or method two;

[0092] The method 1 comprises:

[0093] Li x A s Mn 1-s P 1-z E z O4 (such as Li x FePO4) and Li y MO d (For example, Li y NiO2) and calcined to obtain a positive electrode material for a lithium secondary battery;

[0094] The second method comprises:

[0095] Li x A s Mn 1-s P 1-z E z O4 (such as Li x FePO4) is mixed with any one selected from a lithium source and a source of an M element (e.g., a nickel source), and roasted to obtain an intermediate product;

[0096] The intermediate product is mixed with another selected from a lithium source and a source of an M element (such as a nickel source), and calcined to obtain a positive electrode material for a lithium secondary battery;

[0097] The positive electrode material for lithium secondary battery comprises a core and a coating layer covering the core; the core comprises Li x A s Mn1-s P 1-z E z O4, where 0 < x ≤ 1.1, 0 < s ≤ 1, 0 ≤ z ≤ 0.1, and the A includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge; the E includes one or more elements selected from B (boron), S, Si, N; the coating layer includes Li y MO d , where 1 < y ≤ 6, 1 < d ≤ 4, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, Cr, and the valence state of at least one metal element in the M is lower than its highest oxidation state;

[0098] Optionally, the core contains Li x FePO4, where 0 < x ≤ 1, for example, x is 0.1, 0.2, 0.4, 0.5, 0.7, 0.8, 0.9, 1 or a range composed of any of the above values; the coating layer contains Li y NiO2, where 1 < y < 2, and y is, for example, 1.1, 1.2, 1.5, 1.8 or a range composed of any of the above values.

[0099] Thus, in this application, by using a coating layer containing a lithium supplement agent Li y MO d to coat the core containing the cathode active material Li x A s Mn 1- s P 1-z E z O4, the uniformity of the distribution of the lithium supplement agent in the cathode material is improved, the contact area between the lithium supplement agent and the electrolyte is increased, the conductivity of the cathode material is enhanced, the polarization degree is reduced, the lithium extraction amount of the cathode material is increased, and the energy density of the battery cell is improved.

[0100] In some embodiments, in Method 1,

[0101] The Dv50 particle size of the Li y MO d (such as Li y NiO2) is 8 - 25 nm, optionally 8 - 10 nm, for example, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 15 μm, 16 μm, 17 μm, 18 μm, 20 μm, 22 μm, 23 μm, 24 μm, 25 μm; and / or,

[0102] The Li x A s Mn1-s P 1-z E z O4 (such as Li x FePO4) has a Dv50 particle size of 0.1-10 μm, optionally 0.5-5 μm, such as 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any range thereof; and / or,

[0103] The Li y MO d (For example, Li y NiO2) and the Li x A s Mn 1-s P 1-z E z O4 such as Li x The mass proportion of FePO4 is 0.5%-8%, and can be 1%-5%, such as 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or any range thereof; and / or,

[0104] The calcination temperature is 400°C-1200°C, and may be 600°C-1200°C, such as 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C or any range thereof; and / or,

[0105] The calcination time is 30-65 hours, for example, 30, 35, 40, 45, 50, 55, 60, 65 hours or any range thereof; and / or,

[0106] Mixing is performed by a coating machine at a speed of 50-400 rpm, such as 50 rpm, 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm or any range thereof; and / or,

[0107] The mixing time is 3-10 hours, for example 3, 4, 5, 6, 7, 8, 9, 10 hours or any range thereof; and / or,

[0108] The method 1 further comprises: before mixing, coating the Li y MO d (For example, Li y NiO2) and / or Li x A s Mn 1-s P 1-z E z O4.

[0109] Therefore, through Li y MO d and Li x A s Mn 1-s P 1-z E z O4 is formulated with the above-mentioned particle size ratio. On the one hand, it can regulate the rate performance of the material, and on the other hand, it can maintain a balance between the initial lithium removal amount and the subsequent lithium release amount, and avoid the introduction of residual alkali, thereby improving the energy density of the battery cell and extending the cycle life of the battery.

[0110] In the present invention, Dv50 particle size refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. Dv50 particle size is tested by conventional methods in the art. For example, according to GB / T 19077-2016 "Particle Size Distribution Laser Diffraction Method", the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd. of the United Kingdom is used for determination.

[0111] In some embodiments, in the method 2,

[0112] The lithium source includes one or more of lithium hydroxide, lithium oxide, and lithium carbonate; and / or,

[0113] The source of the M element includes one or more of the hydroxide, sulfate, nitrate, chloride, and oxide of the M element; and / or,

[0114] The calcination temperature is independently 400°C-800°C, such as 400°C, 500°C, 600°C, 700°C, 800°C or any range thereof; and / or,

[0115] The calcination time is independently 30-65 hours, for example 30, 35, 40, 45, 50, 55, 60, 65 hours or any range thereof; and / or,

[0116] Mixing is performed by a coating machine, and the rotation speed used for mixing is independently 300-400 rpm, such as 300 rpm, 350 rpm, 400 rpm or a range consisting of any of the above values; and / or,

[0117] The mixing time is independently 4-6 hours, such as 4, 4.5, 5, 5.5, 6 hours or a range consisting of any of the above values.

[0118] [Positive electrode]

[0119] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the aforementioned positive electrode material or the positive electrode material prepared by the aforementioned method.

[0120] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0121] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0122] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0123] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0124] In some embodiments, the positive electrode material may also adopt positive electrode materials for batteries that are well known in the art. As an example, it may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0125] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0126] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0127] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0128] [Method of using battery cells]

[0129] One embodiment of the present application provides a method for using a battery, which is charged with an upper limit voltage in the range of 3.65-3.85V (for example, 3.65V, 3.68V, 3.7V, 3.73V, 3.75V, 3.8V, 3.82V or a range composed of any of the above numerical values), and optionally discharged with a lower limit voltage in the range of 2.0-2.5V (for example, 2.1V, 2.2V, 2.3V, 2.4V or a range composed of any of the above numerical values); wherein the battery includes the aforementioned positive electrode material, the positive electrode material prepared by the aforementioned method, or the aforementioned positive electrode sheet.

[0130] In this way, the oxidative decomposition of the electrolyte can be reduced, and some active lithium ions retained in the lithium supplement can be gradually released in subsequent cycles, thereby extending the cycle life of the battery.

[0131] In some embodiments, the upper limit voltage of charging is also called the charging cut-off voltage; the lower limit voltage of discharging is also called the discharging cut-off voltage.

[0132] [Negative electrode]

[0133] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.

[0134] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0135] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0136] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0137] In some embodiments, the negative electrode film layer may further include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0138] In some embodiments, the negative electrode film layer may further include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0139] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0140] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0141] [Electrolytes]

[0142] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0143] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0144] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0145] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0146] In some embodiments, the electrolyte may further include additives. As examples, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0147] [Isolation film]

[0148] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0149] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0150] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0151] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0152] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0153] In some embodiments, the charging upper limit voltage (also called the charging cut-off voltage) of the battery is 3.65-3.85V, for example, 3.65V, 3.68V, 3.7V, 3.73V, 3.75V, 3.8V, 3.82V or any range consisting of the above values; optionally, the discharge lower limit voltage (also called the discharge cut-off voltage) of the battery is 2.0-2.5V, for example, 2.1V, 2.2V, 2.3V, 2.4V or any range consisting of the above values.

[0154] In this way, the oxidative decomposition of the electrolyte can be reduced, and some active lithium ions retained in the lithium supplement can be gradually released in subsequent cycles, thereby extending the cycle life of the battery.

[0155] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0156] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0157] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0158] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0159] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0160] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0161] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0162] In addition, the present application also provides an electrical device, which includes at least one of the battery cells, battery modules, or battery packs provided in the present application. The battery cells, battery modules, or battery packs can be used as power sources for electrical devices, or as energy storage units for electrical devices. Electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0163] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0164] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of battery cells, a battery pack or a battery module can be used.

[0165] [Example]

[0166] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0167] Example 1

[0168] (1) Preparation of positive electrode materials:

[0169] The volume average particle size Dv50 is 8 μm and the BET specific surface area is 0.55 m 2 / g lithium supplement Li 1.8 NiO2 was crushed by a high-speed pulverizer at a speed of 700-800 rpm for 5-8 hours to obtain particles with a volume average particle size Dv50 of 8-10 nm; the volume average particle size Dv50 was 2 μm and the BET specific surface area was 10.5 m 2 / g LiFePO4 and the crushed lithium supplement agent are put into a coating machine and mixed evenly at a speed of 300-400rpm for 2-3 hours. The mass ratio of the lithium supplement agent to the positive electrode active material is 2%. The mixture is calcined at 600-1200℃ for 30-65 hours to obtain a positive electrode material.

[0170] (2) Preparation of positive electrode sheet: positive electrode material, conductive agent acetylene black, and binder PVDF (polyvinylidene fluoride) are mixed in a weight ratio of 97:1:2, and solvent N-methylpyrrolidone is added. The mixture is stirred thoroughly to obtain positive electrode slurry, which is then coated on the surface of the positive electrode current collector aluminum foil. After drying and cold pressing, the positive electrode sheet is obtained.

[0171] (3) Preparation of negative electrode sheet: Graphite, conductive agent carbon black, sodium carboxymethyl cellulose, and styrene polybutadiene rubber are mixed in a weight ratio of 96:1:1:2, and solvent water is added. The mixture is stirred thoroughly to obtain a negative electrode slurry, which is then coated on the surface of the negative electrode current collector copper foil. After drying and cold pressing, a negative electrode sheet is obtained.

[0172] (4) Isolation film: Polypropylene film is used.

[0173] (5) Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed at a volume ratio of 1:1:1, and then LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte. The concentration of LiPF6 in the electrolyte was 1 mol / L.

[0174] (6) Preparation of secondary batteries: stack and wind the above-mentioned positive electrode sheets, separators, and negative electrode sheets in order to obtain an electrode assembly; place the electrode assembly in an outer package, add the above-prepared electrolyte, and obtain a secondary battery after packaging, standing, forming, aging, and other processes.

[0175] The secondary battery preparation methods of Examples 2-26 and Comparative Examples 1-2 are similar to those of Example 1. The preparation methods of different products are shown in Table 1, and the product parameters are shown in Table 2.

[0176] Preparation method of the positive electrode material of Example 4:

[0177] The volume average particle size Dv50 is 2 μm and the BET specific surface area is 10.5 m 2 / g of positive electrode active material LiFePO4 and lithium hydroxide (volume average particle size Dv50 is 0.1-0.5μm, LiOH content>99.0%, Li2CO3<1%) accounting for 2.1% of the mass of the positive electrode active material are first mixed in a high-speed coating machine at a speed of 300-400rpm for 4-6 hours, and calcined at 400-800℃ for 30-40 hours to form a lithium source coated lithium iron phosphate material, and then the lithium iron phosphate material coated with the lithium source is mixed with a lithium hydroxide having a volume average particle size Dv50 of 2-4μm and a BET specific surface area of ​​7.85m 2 / g of nickel oxide is mixed, the mass ratio of nickel oxide to lithium hydroxide is 11:10, the mixture is mixed at a rotation speed of 300-400rpm for 4-6 hours in a coating machine, and the calcination time is 400-800℃ for 30-65 hours.

[0178]

[0179]

[0180]

[0181]

[0182]

[0183]

[0184]

[0185]

[0186]

[0187] Material testing and battery testing

[0188] (1) Test of the average diameter of the core and the average thickness of the coating:

[0189] TEM is used to test the positive electrode material. Since the core and coating of a single material particle present different lattices under TEM, the interface between the core and the coating can be observed. Combined with mapping (TEM's built-in software), the core diameter and coating thickness of a single material particle are measured. A total of 50-60 material particles are measured, and the average core diameter and coating thickness of all material particles are calculated to obtain the average core diameter and coating thickness.

[0190] (2) Test of volume average particle size Dv50:

[0191] According to GB / T 19077-2016 “Particle size distribution by laser diffraction method”, the Mastersizer 2000E laser particle size analyzer produced by Malvern Instruments Ltd., UK, was used for determination.

[0192] (3) BET specific surface area test:

[0193] The test method refers to the standard GB / T19587-2004 "Determination of specific surface area of ​​solid substances by gas adsorption BET method".

[0194] Take 8-15g of the sample to be tested and put it into the sample tube, and record the initial mass of the sample to be tested. Put the weighed sample to be tested into the specific surface area analyzer TRISTAR II 3020, then start degassing, and heat the sample to be tested to 200℃, keep it for 2h, and then record the mass of the sample to be tested after degassing. Then reload the degassed sample to be tested into the equipment, pour in liquid nitrogen for BET test. Set the nitrogen pressure to 0.08MPa-0.12MPa. After the test, calculate the BET specific surface area from the test results.

[0195] (4) Test of the initial lithium removal of the positive electrode:

[0196] The positive electrode sheet and the lithium metal sheet are assembled into a buckle battery, and the buckle battery is charged from 2.0V to 3.7V at 0.1C to obtain the first charge capacity. The ratio of the first charge capacity to the mass of the positive electrode material is the first lithium removal amount.

[0197] (5) The first coulombic efficiency test of positive electrode materials:

[0198] The positive electrode sheet and the lithium metal sheet are combined into a buckle battery, and the buckle battery is charged from 2.0V to 3.7V at 0.1C to obtain the first charge capacity, and then the buckle battery is discharged from 3.7V to 2.0V at 0.1C to obtain the first discharge capacity. The ratio of the first discharge capacity to the first charge capacity is the first coulomb efficiency of the positive electrode material.

[0199] (6) Specific capacity test of secondary battery:

[0200] The secondary battery is charged from 2.0V to 3.65V at 0.1C, then discharged to 2.0V at 0.1C. After standing for 5 minutes, it is discharged to 2.0V at 0.05C. The discharge capacity obtained is the capacity of the secondary battery. The discharge capacity divided by the mass of the secondary battery positive electrode material is the specific capacity of the secondary battery.

[0201] (7) Test of the cycle capacity retention rate of secondary batteries:

[0202] In a constant temperature environment of 60°C, the secondary battery was charged from 2.0V to 3.65V at 0.1C, then charged to 0.05C at a constant voltage of 3.65V, then discharged to 2.0V at 1C, left to stand for 5 minutes, and then discharged to 2.0V at 0.05C to obtain the discharge capacity. The charge and discharge cycle was performed according to the above process for a total of 1000 cycles, and the discharge capacity of the last cycle was divided by the discharge capacity of the third cycle to obtain the cycle capacity retention rate of 1000 cycles.

[0203] Reference secondary battery: The positive electrode material of the reference secondary battery corresponding to each embodiment or comparative example is only LiFePO4, the total weight of the positive electrode material is the same as that in the embodiment or comparative example, and the rest is the same as that in the embodiment or comparative example. The cycle capacity retention rate of the reference secondary battery after 1000 cycles is determined according to the above method.

[0204] The cycle capacity retention rate of the secondary battery after 1000 cycles was subtracted from the cycle capacity retention rate of the reference secondary battery after 1000 cycles to obtain the improvement value of the cycle capacity retention rate.

[0205] Table 3: Performance test results of Examples 1-26 and Comparative Examples 1-2

[0206]

[0207]

[0208] From Table 1-3 we can see that:

[0209] Compared with Comparative Example 1 which uses Li2NiO2 as a lithium supplement, the positive electrode material of Example 1 of the present application has a higher initial lithium removal amount, a higher battery cell energy density, and a longer battery cycle life.

[0210] Compared with Comparative Example 2 in which the lithium supplement agent is directly mixed with the positive electrode active material, the cycle life of the batteries in Examples 1-5 and 8-14 of the present application is longer.

[0211] Compared with the case of Example 15 using a lower average core diameter, the cycle life of the batteries of Examples 1-3 and 8-14 of the present application is longer. Compared with the case of Example 16 using a higher average core diameter, the positive electrode materials of Examples 1-3 of the present application have a higher initial lithium removal amount, a higher cell energy density, a longer cycle life of the battery, and a higher initial coulombic efficiency.

[0212] Compared with Example 17, which uses a lower lithium supplement and positive electrode active material mass ratio, the positive electrode materials of Examples 1, 6-7 of the present application have a higher initial lithium removal amount, a higher battery cell energy density, and a longer battery cycle life. Compared with Example 18, which uses a higher lithium supplement and positive electrode active material mass ratio, the positive electrode materials of Examples 1, 6-7 of the present application have a higher initial lithium removal amount and a higher battery cell energy density.

[0213] Compared with Example 19 which adopts a charge and discharge voltage range of 2.0-4.2V, the battery in Example 1 of the present application has a longer cycle life and a higher first coulombic efficiency.

[0214] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode material for a lithium secondary battery, comprising a substrate and a modified body arranged on the surface of the substrate; the substrate comprises Li x A s Mn 1-s P 1-z E z O4, where 0 < x ≤ 1.1, 0 < s ≤ 1, 0 ≤ z ≤ 0.

1. A includes one or more elements of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge. E includes one or more elements of B (boron), S, Si, N. The modifier includes Li y MO d , where 1 < y ≤ 6, 1 < d ≤ 4. M includes one or more elements of Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, Cr. The valence state of at least one metal element in M is lower than its own highest oxidation state.

2. The positive electrode material according to claim 1, comprising a core and a coating layer covering the core; the core comprises Li x A s Mn 1-s P 1-z E z O4, where 0 < x ≤ 1.1, 0 < s ≤ 1, 0 ≤ z ≤ 0.1, A includes one or more elements of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge, and E includes one or more elements of B (boron), S, Si, N; the coating layer includes Li y MO d , where 1 < y ≤ 6, 1 < d ≤ 4, M includes one or more elements of Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, Cr, and the valence state of at least one metal element in M is lower than its own highest oxidation state.

3. The positive electrode material according to claim 1 or 2, wherein The modified body or the coating layer includes Li y MnO2、Li y NbO4、Li y FeO4、Li y CoO4、Li y NiO2、Li y CuO2、Li y Cu x1 Ni 1-x1-y1 M' y1 O2, wherein the y is independently greater than 1 and less than or equal to 6, 0<x1<1, 0≤y1<0.1, and M' comprises one or more elements of Zn, Sn, Mg, Fe, and Mn; Optionally, the modified body or the coating layer includes Li 1.8 MnO2, Li6CoO4, Li y NiO2、Li2Cu 0.6 Ni 0.4 One or both of O2.

4. The positive electrode material according to any one of claims 1 to 3, wherein The matrix or the core includes Li x D s1 Fe s2 Mn 1-s1-s2 PO4, where 0 < x ≤ 1, s1 ≥ 0, s2 > 0, 0 < s1 + s2 ≤ 1; the D includes one or more elements of Ti, V, Zr, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge, and may optionally include one or two elements of Ti and V; the modifier or the coating layer includes Li y NiO2, where 1 < y < 2.

5. The positive electrode material according to any one of claims 1 to 4, wherein The average diameter of the matrix or the core is 0.7-12 μm, optionally 1-10 μm; and / or, The average thickness of the modified body or the coating layer is 10-30 nm, and can be 10-15 nm.

6. The positive electrode material according to any one of claims 1 to 5, wherein The Li y MO d With the Li x A s Mn 1-s P 1- z E z The mass proportion of O4 is 0.5%-8%, and can be optionally 1%-5%.

7. The positive electrode material according to any one of claims 1 to 6, wherein The BET specific surface area of ​​the positive electrode material is 0.9-11.1 m 2 / g, optional 7-10.7m 2 / g.

8. The positive electrode material according to any one of claims 1 to 7, wherein The modified body or the coating layer further comprises a carbonaceous material, wherein the carbonaceous material is coated on the Li y MO d surface; and / or, The matrix or the core also includes a carbonaceous material, and the carbonaceous material is coated on the Li x A s Mn 1-s P 1-z C z O4 surface; and / or, the carbonaceous material includes one or more of conductive carbon, graphene, and carbon nanotubes.

9. A method for preparing a positive electrode material for a lithium secondary battery, which is method 1 or method 2; The method 1 comprises: Li x A s Mn 1-s P 1-z E z O4 and Li y MO d Mixing and calcining to obtain a positive electrode material for a lithium secondary battery; The second method comprises: Li x A s Mn 1-s P 1-z E z O4 is mixed with any one selected from a lithium source and a source of an M element, and roasted to obtain an intermediate product; The intermediate product is mixed with another source selected from a lithium source and a source of an M element, and calcined to obtain a positive electrode material for a lithium secondary battery; Among them, the positive electrode material for the lithium secondary battery includes a core and a coating layer that coats the core; the core includes Li x A s Mn 1-s P 1-z E z O4, where 0 < x ≤ 1.1, 0 < s ≤ 1, 0 ≤ z ≤ 0.1, the A includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Ge, and the E includes one or more elements selected from B (boron), S, Si, N; the coating layer includes Li y MO d , where 1 < y ≤ 6, 1 < d ≤ 4, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, Cr, and the valence state of at least one metal element in the M is lower than its own highest oxidation state.

10. The method according to claim 9, wherein: In the method 1, The Li y MO d The Dv50 particle size is 8-25 nm, optionally 8-10 nm; and / or, The Li x A s Mn 1-s P 1-z E z The Dv50 particle size of O4 is 0.1-10 μm, optionally 0.5-5 μm; and / or, The Li y MO d With the Li x A s Mn 1-s P 1-z E z The mass proportion of O4 is 0.5%-8%, optionally 1%-5%; and / or, The calcination temperature is 400°C-1200°C, and can be 600°C-1200°C; and / or, The calcination time is 30-65 hours; and / or, Mixing is performed by a coating machine at a speed of 50-400 rpm; and / or, The mixing time is 3-10 hours; and / or, The method 1 further comprises: before mixing, coating the Li y MO d and / or Li x A s Mn 1-s P 1-z E z O4; and / or, The carbonaceous material includes one or more of conductive carbon, graphene, and carbon nanotubes.

11. The method according to claim 9, wherein: In the second method, The lithium source includes one or more of lithium hydroxide, lithium oxide, and lithium carbonate; and / or, The source of the M element includes one or more of the hydroxide, sulfate, nitrate, chloride, and oxide of the M element; and / or, The calcination temperature is independently 400°C-800°C; and / or, The calcination time is independently 30-65 hours; and / or, Mixing is performed by a coating machine, and the speed of mixing is independently 300-400 rpm; and / or, The mixing time was independently 4-6 hours. 12 . A positive electrode sheet, comprising the positive electrode material according to claim 1 or the positive electrode material prepared by the method according to claim 9 .

13. A secondary battery comprising the positive electrode sheet according to claim 12.

14. The secondary battery according to claim 13, wherein The upper limit voltage of the secondary battery is 3.65-3.85V; Optionally, the lower discharge limit voltage of the secondary battery is 2.0-2.5V.

15. An electrical device comprising the secondary battery according to claim 13 or 14.

16. A method of using a secondary battery, wherein the battery is charged at an upper voltage in the range of 3.65-3.85V and optionally discharged at a lower voltage in the range of 2.0-2.5V; wherein: The secondary battery comprises the positive electrode sheet according to claim 12.

Citation Information

Cited By

  • Positive electrode material for lithium secondary battery and preparation method therefor, positive electrode sheet, secondary battery and use method therefor, and electric device

    EP4773226A1